An examination of mood changes and performance in a professional basketball team - Hoffman, J. R.; Bar-Eli, M.; Tenenbaum, G. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: The purpose of this study was to examine the relationship between the Profile of Mood States (POMS) and performance in a professional basketball team. METHODS: Participants: seven male professional basketball players playing for the defending champions of the Israel Basketball League participated in this study. Experimental design: the POMS was administered seven times (T1-T7) during the season. The initial POMS administration was performed three weeks following the start of preseason practice and one day prior to the first basketball game. Each of the other POMS administrations were performed two days following a game and no more than 2 days before the next game. RESULTS: Typical iceberg profiles were observed during T1, T2 and T3, which coincided with successful performance (winning percentages greater than 60% between each POMS administration). Subsequent decreases in performance between T3 and T4 (a 33% winning percentage) resulted in a decrease in vigor and an increase in anger. As team performance improved between T4 and T5 (winning percentage again above 60%), vigor returned to its original level. However, the mood states anger and depression remained elevated, even during successful team play. This may have been related to problems independent of basketball performance (coaching and financial). CONCLUSIONS: These results suggest that the mood state vigor may be reflective of team performance. In addition, mood states appear to be influenced more by performance or experience, rather than performance being influenced by changes in mood states.